Russia's War of Aggression against Ukraine "Zeitenwende" for German Security Policy - Hansen, Stefan; Husieva, Olha; Frankenthal, Kira (ISPK-Studien zur Konfliktforschung, 2023)
The Russian war of aggression against Ukraine represents a Zeitenwende - a turning point - in German foreign and security policy, which requires a complete redefinition of Germany's role within the future European security order. Through contributions by renowned experts, this anthology provides information on the causes, developments and foreseeable consequences of the Russian war of aggression. This open access book will appeal to scholars, decision-makers, students, and anyone interested in international politics, conflict studies, and military-strategic dimensions of the Russian-Ukrainian war.